Coupled bending-torsion flutter investigation of MRE tapered sandwich blades in a turbomachinery cascade. (July 2020) - Bornassi, S.; Navazi, H.M.; Haddadpour, H.
Abstract: This paper studies the effects of bending-torsion coupling on the flutter stability boundaries of a turbomachinery cascade with Magnetorheological Elastomer (MRE) based sandwich blades. The blade structure is considered as a non-uniform sandwich beam with an embedded MRE core. The governing equations of bending and torsional motions are obtained based on the classical sandwich beam theory and the unsteady Whitehead aerodynamic theory is applied for modeling of the aerodynamic flow. The equations of motion governing on the coupled aeroelastic system have been derived in a discrete form by Lagrange's equations and using the assumed modes method. The stability analysis is performed and the effects of various parameters such as coupling, magnetic field, taper ratios and different mistuning patterns on the flutter characteristics have been investigated. The results indicate that the flutter stability is clearly affected by the interaction between the bending and torsional motions which is in agreement with the results previously obtained for a typical cascade. The results also indicate that the change of blade cross sectional area has a significant effect on the flutter boundaries. Highlights: Coupled bending-torsion flutter of a turbomachinery cascade with MRE tapered sandwich blades is studied. Lower stability margins are predicted for the coupled system compared to the uncouple system. The stability of the system significantly improves with increasing magnetic field. Tapering of the blade cross section results in more or less stability depending on the tapering pattern. Alternate mistuning has more stabilizing effects than the random mistuning.